THU0061 Correlations Between Angiogenic Factors and Capillaroscopic Patterns in Systemic Sclerosis. (23rd January 2014) - Avouac, J.; Vallucci, M.; Smith, V.; Senet, P.; Ruiz, B.; Sulli, A.; Pizzorni, C.; Frances, C.; Chiocchia, G.; Cutolo, M.; Allanore, Y.
Abstract : Objectives: To assess whether nailfold videocapillaroscopy (NVC) changes are associated with peripheral blood or serum levels of angiogenic biomarkers in systemic sclerosis (SSc). Methods: Endothelial markers were first assessed in a discovery cohort of 60 SSc patients consecutively recruited. Circulating endothelial progenitor cells (EPCs) and circulating endothelial cells (CECs) were quantified in peripheral blood by flow cytometry after cell sorting, as previously described (1 ). Serum levels of vascular endothelial growth factor (VEGF), placenta growth factor (PlGF), soluble vascular adhesion molecule (sVCAM), endothelin-1 (ET1), angiopoietin-2, endoglin, endostatin and Tie-2, were measured by quantitative sandwich enzyme-linked immunosorbent assay (ELISA) technique (Quantikine kits, R&D systems). Serum levels of endothelial markers that were found associated with NVC patterns in the discovery cohort were then measured in a replication cohort of 43 SSc patients. NVC was performed by two independent examiners and images were analysed anonymously by four investigators blinded for the clinical and serum status of SSc patients and classified as early, active and late pattern (2 ). Results: The mean ± standard deviation (SD) age of the 60 patients (46 women) was 56±13 year old and the mean ± SD disease duration was 9±8 years at baseline. Thirty-six patients had the diffuse cutaneous subset, and 24 the limited. 14 (23%) and 8 (18%) patients had an early, 22 (37%) and 20 (46%) an active, and 24 (40%) and 15 (35%) a late NVC pattern in the discovery and replication cohorts, respectively. By univariate analysis focused on biomarkers, patients with late NVC pattern exhibited significantly lower EPC levels and higher VEGF serum levels than patients with early and active patterns (p<0.0001 and p=0.01, respectively). Significantly higher VEGF levels in the late NVC pattern were confirmed in the replication cohort (p=0.01) and in the combined cohort of 103 patients (p=0.003). In the discovery cohort, endothelin serum levels were significantly higher in the active pattern compared to early and late patterns (p=0.02). This result was not confirmed in the replication cohort. In multivariate multiple regression analysis, lower EPC and higher VEGF levels were independently associated with the late NVC pattern (p=0.003 and p=0.001 respectively). In an alternate multivariate model including these 2 biomarkers and SSc-related disease characteristics, lower EPC counts (p=0.005), higher VEGF levels (p=0.01), history of digital ulcers (p=0.04), and a modified Rodnan skin score >14 (p<0.0001) were independently associated with the late NVC pattern. Conclusions: Our data revealed decreased EPC counts in patients with the late NVC pattern, suggesting that deficient vasculogenesis may contribute to the severe capillary loss observed at this stage. VEGF upregulation in the late pattern may appear as an attempt of compensatory mechanism to stimulate deficient vasculogenesis. Further studies are now needed to determine the role of VEGF and EPCs in endothelial injury and repair in SSc. References: Avouac et al, Ann Rheum Dis 2008, Cutolo M et al. J Rheumatol. 2000 Disclosure of Interest: J. Avouac Grant/research support from: Actelion, Pfizer, M. Vallucci: None Declared, V. Smith: None Declared, P. Senet: None Declared, B. Ruiz: None Declared, A. Sulli: None Declared, C. Pizzorni: None Declared, C. Frances: None Declared, G. Chiocchia: None Declared, M. Cutolo: None Declared, Y. Allanore Grant/research support from: Actelion, Pfizer